2018
DOI: 10.1007/s10620-017-4905-3
|View full text |Cite
|
Sign up to set email alerts
|

Proton Pump Inhibitors Increase the Susceptibility of Mice to Oral Infection with Enteropathogenic Bacteria

Abstract: Laz raised susceptibility to C. rodentium as increased numbers of the pathogen reach the site of infection. Our results suggest that it was due to increased stomach pH which allowed more peroral enteropathogens to pass the stomach, but not because of changes of intestinal environment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
5
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 47 publications
4
5
0
1
Order By: Relevance
“…The results of two mouse studies suggest that reduced bactericidal effect, due to increased stomach pH, may be the most important factor for increased enteric infection risk. Mice received PPIs 7 days prior to infection with the murine pathogen Citrobacter rodentium, which resulted in increased numbers of C. rodentium organisms in the cecum 1 h postinoculation compared to control mice (96). Similar results were observed in another study, where treatment of mice with PPIs led to increased colonization by vancomycin-resistant enterococci and Klebsiella pneumoniae (97).…”
Section: Proton Pump Inhibitorssupporting
confidence: 71%
“…The results of two mouse studies suggest that reduced bactericidal effect, due to increased stomach pH, may be the most important factor for increased enteric infection risk. Mice received PPIs 7 days prior to infection with the murine pathogen Citrobacter rodentium, which resulted in increased numbers of C. rodentium organisms in the cecum 1 h postinoculation compared to control mice (96). Similar results were observed in another study, where treatment of mice with PPIs led to increased colonization by vancomycin-resistant enterococci and Klebsiella pneumoniae (97).…”
Section: Proton Pump Inhibitorssupporting
confidence: 71%
“…Upon ingestion of contaminated food or water, EPEC and EHEC initially enter the stomach. Acidity of the gastric fluid not only aids the host in digestion of food but also serves as a significant barrier to enteric infection (Pienaar, Singh, & Barnard, 2019;Yasutomi et al, 2018). EPEC has the ability to withstand and recover from exposure to simulated gastric fluid (Pienaar et al, 2019).…”
Section: The Physical Landscape and Ae Pathogensmentioning
confidence: 99%
“…However, during EHEC infection, 20-80% of ingested bacteria are estimated to die before reaching the small intestine (Takumi, de Jonge, & Havelaar, 2000). Neutralising the stomach acid of mice by treating the animals with proton pump inhibitor (PPI) lansoprazole before infection with C. rodentium, and thereby attenuating this barrier, increased murine susceptibility to C. rodentium by allowing more bacteria to survive and reach the infection site, resulting in colitis symptoms in response to a 10-fold lower infectious dose (Yasutomi et al, 2018). A retrospective human case-control study confirmed that patient exposure to PPIs is a significant risk factor for Enterobacteriaceae infection (Cunningham, Jones, Enki, & Tischhauser, 2018).…”
Section: The Physical Landscape and Ae Pathogensmentioning
confidence: 99%
“…As previously described by Yasutomi et al (11), mice were unfed for 2 d with no solid food but provided water up until 2 h prior to experiments. TM inh -23 (10 mg/kg), lansoprazole (10 mg/kg), or vehicle was administered intraperitoneally 6 h and 30 min prior to stomach excision.…”
Section: Gastric Fluid Phmentioning
confidence: 99%